Melting the Cultural Iceberg in Indigenizing Higher Education: Shifts to Accountability in Times of Reconciliation. (5th March 2019) - Vaudrin‐Charette, Julie
Abstract: In this chapter, the author draws on personal experiences as pedagogical advisor and as a doctoral student, to consider how recognizing voice, family, and vulnerabilities may assist in developing a sense of accountability in academia. Reflecting on the Canadian context of reconciliation, the author considers how moving from an intercultural to an equity paradigm may melt the cultural iceberg.